2020
DOI: 10.1016/j.acalib.2020.102234
|View full text |Cite
|
Sign up to set email alerts
|

Boolean redux: Performance of advanced versus simple boolean searches and implications for upper-level instruction

Abstract: Building off an earlier study, which examined whether or not it was beneficial to teach Boolean logic to introductory students, the present study examines the efficacy of Boolean OR searching in more advanced search strategies, for example, capstone projects and graduate theses and dissertations. Results show that both simple and advanced Boolean searches yield relevant results. Based on relevance, there is no compelling evidence that either search is superior. To capture all the literature on a topic, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Primo was not included in Lowe et al's 2018 study but assuming their results hold for Primo, this further supports the simplification of an initial encounter with a search interface. In a study comparing relevance and overlap of simple Boolean and advanced Boolean Lowe et al (Lowe et al, 2020) found that simple Boolean actually outperformed advanced Boolean overall. When one considers the fact that the Basic Search mode in Primo returns the exact same results for explicitly typed Boolean queries using nested parentheses as it does when those same queries are executed using the Advanced Search mode, the case against having a complex search interface on a homepage is closed.…”
Section: The Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primo was not included in Lowe et al's 2018 study but assuming their results hold for Primo, this further supports the simplification of an initial encounter with a search interface. In a study comparing relevance and overlap of simple Boolean and advanced Boolean Lowe et al (Lowe et al, 2020) found that simple Boolean actually outperformed advanced Boolean overall. When one considers the fact that the Basic Search mode in Primo returns the exact same results for explicitly typed Boolean queries using nested parentheses as it does when those same queries are executed using the Advanced Search mode, the case against having a complex search interface on a homepage is closed.…”
Section: The Discussionmentioning
confidence: 99%
“…These researchers discovered that Boolean is not "better" than natural language/phrase searching (p. 529). Subsequent work by Lowe et al (Lowe et al, 2020) continued to explore researchers' habits and behaviors related to searching, finding that "based on relevance, there is no compelling evidence that either search is superior" and that "simple search is likely to be much more realistic in anticipating a student approach" (p. 5). Those researchers supported their findings noting the congruity with other recent studies, citing students' difficulty in finding information such as defining search terms and using discipline-specific databases.…”
Section: On the Present Situationmentioning
confidence: 99%
“…The Scopus database was searched using simple and advanced Boolean logic concepts. It was then filtered to obtain as many articles as possible relevant to the research objectives [72]. The search result was filtered according to publication year, subject area, document type, and source type and restricted to English language peerreviewed journals and articles.…”
Section: Identifying Electronic Databases and Eligibility Criteriamentioning
confidence: 99%
“…Search keywords included 'pre-service teacher', 'identity', 'personal identity' and 'professional identity'. Using the Boolean search strategy (Lowe et al, 2020), Te Waharoa and Google Scholar databases were searched for empirical, peer-reviewed journal articles, published in English between 2012-2022. Search strings and joining keywords using "AND" increased relevant search results.…”
Section: Review Of Literaturementioning
confidence: 99%